Pricing in the medical sector: Theoretical foundations and practical aspects - Serhiy Inozemtsev (University Economic Bulletin, 2024)
Pricing is one of the components of ensuring competitive conditions in the market: it has its own specificity in the healthcare market, which is characterized by various forms of operation of enterprises, access to goods and services. The purpose of the study was to investigate the methods and approaches to this process in Ukraine, taking into account the peculiarities of the country's development related to the full-scale invasion of the Russian Federation. The methods used in the study were formal and legal (to form logical links between individual regulatory documents) and comparison (to assess the specifics of pricing in the medical sector in different countries). The study assessed the pricing process as such and described the factors that influence it in practice in general and in the medical sector. It was also concluded that understanding the role of this process for both the state and potential clients is important, as it affects economic stability, quality of medical services, social justice. Particular attention was paid to such approaches as "cost+markup" and "market-based". Based on the models built in this paper, it was concluded that these approaches should be used in symbiosis (to focus on both market conditions and the company's goals for forming a margin). Attention was also paid to the Value-Based Pricing approach: it was concluded that it is inherently different from the other two approaches, as it requires much more complex estimates, since it is based on the expected utility of the created product. The study also highlighted the problem of non-transparent pricing as one of the main ones that prevents the formation of effective market conditions. The results obtained in the study can be used both to formulate public policy and to create strategies for individual companies in the Ukrainian market of medical goods and services
Keywords: 330; microeconomics; healthcare; public policy; innovation; market configurations